Triterpenoids and steroids isolated from Anatolian Capparis ovata and their activity on the expression of inflammatory cytokines - Isil Gazioglu; Sevcan Semen; Ozden Ozgun Acar; Ufuk Kolak; Alaattin Sen; Gulacti Topcu (Taylor & Francis Group, 2020)
Context Capparis L. (Capparaceae) is grown worldwide. Caper has been used in traditional medicine to treat various diseases including rheumatism, kidney, liver, stomach, as well as headache and toothache. Objective To isolate and elucidate of the secondary metabolites of the C. ovata extracts which are responsible for their anti-inflammatory activities. Materials and methods Buds, fruits, flowers, leaves and stems of C. ovata Desf. was dried, cut to pieces, then ground separately. From their dichloromethane/hexane (1:1) extracts, eight compounds were isolated and their structures were elucidated by NMR, mass spectroscopic techniques. The effects of compounds on the expression of inflammatory cytokines in SH-SY5Y cell lines were examined by qRT-PCR ranging from 4 to 96 µM. Cell viability was expressed as a percentage of the control, untreated cells. Results This is a first report on isolation of triterpenoids and steroids from C. ovata with anti-inflammatory activity. One new triterpenoid ester olean-12-en-3β,28-diol, 3β-pentacosanoate (1) and two new natural steroids 5α,6α-epoxycholestan-3β-ol (5) and 5β,6β-epoxycholestan-3β-ol (6) were elucidated besides known compounds; oleanolic acid (2), ursolic acid (3), β-sitosterol (4), stigmast-5,22-dien-3β-myristate (7) and bismethyl-octylphthalate (8). mRNA expression levels as EC10 of all the tested seven genes were decreased, particularly CXCL9 (19.36-fold), CXCL10 (8.14-fold), and TNF (18.69) by the treatment of 26 µM of compound 1 on SH-SY5Y cells. Discussion and conclusions Triterpenoids and steroids isolated from C. ovata were found to be moderate-strong anti-inflammatory compounds. Particularly, compounds 1 and 3 were found to be promising therapeutic agents in the treatment of inflammatory and autoimmune diseases.